Current Trends in Catheter-Directed Therapy for Acute Pulmonary Embolism - Leal, Silvio (2024)
Acute pulmonary embolism is a leading cause of in-hospital and cardiovascular mortality, and it keeps posing important diagnostic and therapeutic challenges. Traditional treatment options such as anticoagulation, thrombolysis, and surgery are increasingly being challenged by new catheter-based procedures, including catheter-directed thrombolysis, mechanical thrombectomy, and pharmacomechanical hybrid techniques. Emerging evidence supports the effectiveness and safety of these percutaneous methods, which may facilitate faster recovery of right ventricular function and hemodynamics in selected patients, with a lower risk of bleeding compared to standard medical therapy. These interventions may be particularly beneficial for high-risk patients for whom thrombolysis is contraindicated or has proven ineffective, as well as for initially stable intermediate-risk patients who experience hemodynamic decline despite appropriate anticoagulation. Nevertheless, significant knowledge gaps continue to impede the optimization of these techniques and limit the shifting of treatment recommendations for acute pulmonary embolism. This paper provides a summary of the various catheter-directed interventions currently available, highlighting their indications, technical considerations, clinical effectiveness, and potential complications, offering a comprehensive overview of their current future trends in the management of acute pulmonary embolism.